2012
DOI: 10.1039/c2an15912k
|View full text |Cite
|
Sign up to set email alerts
|

Paired pulse voltammetry for differentiating complex analytes

Abstract: Although fast-scan cyclic voltammetry (FSCV) has contributed to important advances in neuroscience research, the technique is encumbered by significant analytical challenges. Confounding factors such as pH change and transient effects at the microelectrode surface make it difficult to discern the analytes represented by complex voltammograms. Here we introduce paired-pulse voltammetry (PPV), that mitigates the confounding factors and simplifies the analytical task. PPV consists of a selected binary waveform wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…9,20,24 With this in mind, it has been shown that a modified form of FSCV can improve the pH and dopamine selectivity. 25 However, the chemical selectivity of other voltammetric techniques has not been well-studied yet. Beside FSCV, we have used RPV for dopamine detection in the brain ("differential pulse voltammetry", a variation of RPV using subtraction between up-and down-rectangular pulses).…”
mentioning
confidence: 99%
“…9,20,24 With this in mind, it has been shown that a modified form of FSCV can improve the pH and dopamine selectivity. 25 However, the chemical selectivity of other voltammetric techniques has not been well-studied yet. Beside FSCV, we have used RPV for dopamine detection in the brain ("differential pulse voltammetry", a variation of RPV using subtraction between up-and down-rectangular pulses).…”
mentioning
confidence: 99%
“…3C [17]. PPV consists of triangle-shaped pairs of voltammetric pulses (primary and secondary pulse) with a specific time delay between the two pulses comprising each binary scans, repeated with a negative holding potential between the paired pulses [16]. The primary pulse is defined as the first pulse in the binary scans, and the secondary pulse as the following pulse.…”
Section: Methodsmentioning
confidence: 99%
“…All chemicals were purchased from Sigma-Aldrich (St. Louis). The buffer solution was composed of 150 mM sodium chloride and 12 mM Trizma base at pH 7.4, and was pumped across the CFM at a rate of 2 ml/min [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the original work of Adams and co-workers (Blank 1972, Adams 1972), numerous electrochemical techniques and electrode materials have been investigated for in vivo detection of dopamine. Commonly used techniques include constant potential amperometry, differential pulse voltammery, fast scan cyclic voltammetry and paired pulse voltammetry (Shon 2010, Yoshimi 2011, Suzuki 2007, Jang 2012, Keithley 2011). Carbon and carbon derived microelectrodes and metal (Pt and Au) electrodes have been used as transduction materials (Robinson 2008a, Zachek 2008, Bath 2001).…”
Section: Electrochemical Detection Of Monoamine Neurotransmittersmentioning
confidence: 99%